Cotas na Universidade Federal do Ceará: para quem? - Nascimento, Antônio Joamir Brito do (2011)
This dissertation has two main objectives: the first is to show the reasons for the non-acceptance by CEPE (Board of Education, Research and Extension) against the system of quotas for blacks in the UFC (Federal University of Ceará) in 2005. The second is to demonstrate how a demand for racial quotas may be established based on solid statistical data. The research consisted of a theoretical approach of racism, trying to understand how it has been understood in Brazil since the beginning of the twentieth century. The propositions of institutions that defend positively differentiated opportunities for blacks are here placed in discussion, in particular racial quotas for blacks. The research concluded, through the analysis of a document produced by the Working Group "Affirmative Action Policies" (GTPAA) established by the rector to study the feasibility of implementing a quota system based on race and color as a means of access to courses graduation, that the data shown was actually insufficient to convince CEPE of such need, dethroning the claim that most components of the CEPE were racist. By contrast, the research presents data that can help to structure a future demand for quotas assessment in the UFC, according to the specificity of each undergraduate course.